2009
DOI: 10.2971/jeos.2009.09052
|View full text |Cite
|
Sign up to set email alerts
|

Regenerated gratings

Abstract: Strong regenerated gratings with a maximum grating strength exceeding (40-50) dB are fabricated inside an optical fibre by bulk macro thermal processing ∼ 900˚C using a UV-laser seeded Bragg grating. Further annealing between 1000˚C and 1100˚C leads to a stabilised grating ∼ 18 dB in strength. This suffers no further degradation at 1100˚C for the period monitored, over 4 hours. The potential resolution of this process is demonstrated by regenerating two complex profiles. Phase information is retained between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 23 publications
(31 reference statements)
1
32
0
Order By: Relevance
“…It was reported that RBGs formed in Er 3+ codoped optical fibers can sustain high temperature up to 800°C without reduction of reflection [13]. Canning et al demonstrated that RBGs formed in Boron codoped optical fibers can sustain temperature more than 1000°C without significant grating degradation [14][15][16]. They proposed that glass structural transformation rather than the diffusive interpretation is an efficient alternative approach for the formation of RBGs because of the relaxation of high internal pressures in the hightemperature process.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…It was reported that RBGs formed in Er 3+ codoped optical fibers can sustain high temperature up to 800°C without reduction of reflection [13]. Canning et al demonstrated that RBGs formed in Boron codoped optical fibers can sustain temperature more than 1000°C without significant grating degradation [14][15][16]. They proposed that glass structural transformation rather than the diffusive interpretation is an efficient alternative approach for the formation of RBGs because of the relaxation of high internal pressures in the hightemperature process.…”
Section: Introductionmentioning
confidence: 96%
“…It was shown that fluorine is not necessary and the diffusion of hydroxyl group through the reaction and formation of molecular water could produce a grating as periodic modulation of oxygen. Recently RBGs were also demonstrated in Er 3+ -or boron-codoped germanosilicate optical fibers and highly photosensitive germanium doped fibers [13][14][15][16]. It was reported that RBGs formed in Er 3+ codoped optical fibers can sustain high temperature up to 800°C without reduction of reflection [13].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the past few years, the field of regenerated fibre Bragg gratings (FBGs) has been the subject of intense research activity as this member of the FBG family continues to prove itself as a versatile choice when ultrahigh temperature performance is required [1][2][3][4]. The remarkable stability at extreme temperatures means that regenerated gratings are now finding applications in a wide variety of sensing applications such as diesel locomotive engine temperature regulation [5], assessment of fire damage to concrete building structures [6] and dual pressure/temperature sensing of gas turbines [7].…”
Section: Introductionmentioning
confidence: 99%